Analysis Of Work Productivity And Human Resource Development To Improve Employee Performance Of PT. Cap Mold Engineering Indonesia - Siva Alfian Marra; Aji Tuhagana; Zenita Apriani (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — To enhance work productivity and employee performance at PT. Cap Mold Engineering Indonesia through an analysis of HR development practicesResearch method— Qualitative and descriptive approach to explore human resource development, work productivity, and employee performance.Result— Lack of active training and education programs negatively impacts employee efficiency and company goals at PT. Cap Mold Engineering Indonesia.Conclusion— Implementing a robust human resource development program, particularly in training and education, is crucial to improve employee effectiveness and efficiency, aiming to meet company expectations and targets.